O discurso sobre etnodesenvolvimento quilombola no governo Lula - Silva, Aline Ferreira da (2010)
This paper focuses on analytical official discourses of "Lula government" about the notion of ethnodevelopment maroon. The objective is to develop an analysis on the articulations of these discourses, observing the references which are activated, the correlations established and the meanings that they suggest. Making use of the methodological strategy of discourse analysis, the study moves to an interpretative universe that seeks to understand the set of statements that articulated in the body become the documental reference that reflects the political-government about development of the narrative on ethnic maroon. The intention is to analyze the relationship ethnicity-maroon permeated by a theoretical paradigm that relates it with the notion of development. Among our principal considerations, the text appears for the need of a new standards that may overcome some theoretical reductionism that permeat the analysis on the subject quilombos in the current context. It suggests an opportunity cost which is located in a universe of discussions very diversified and complex, involving international agencies, academic knowledge, social movements; also involving notions of development, citizenship, justice, democracy, which are involved in your current political context.